Pulsed Electromagnetic Field-Assisting Reduced Graphene Oxide-Incorporated Nanofibers for Osteogenic Differentiation of Human Dental Pulp Stem Cells - Juo Lee; Sungmin Lee; Iksong Byun; Myung Chul Lee; Jungsil Kim; Hoon Seonwoo (IEEE Open Journal of Nanotechnology)
In bone tissue engineering, various approaches have been investigated to enhance osteogenic regeneration. Previous studies have predominantly employed scaffolds with aligned structures or reduced graphene oxide (RGO) to facilitate bone regeneration. However, current scaffold designs face limitations in combining structural guidance with effective electromagnetic stimulation. Additionally, delivering localized stimulation within scaffolds remains a challenge in maximizing the potential of these materials for bone regeneration. To address these limitations and strengthen previous approaches, this study presents a novel strategy in tissue engineering for enhanced osteogenic differentiation. RGO-incorporated nanofibers (RGO-NFs) were fabricated via electrospinning a 10% polycaprolactone (PCL) solution with RGO concentrations varying. The random fibers were deposited on a planar surface, while the aligned fibers were deposited on a rotating drum. The morphology and orientation of the fibers were confirmed through electron microscopy. X-ray diffraction spectrometry was employed to confirm the integration of RGO and PCL. All groups demonstrated optimal cell adhesion and viability. RGO-NFs exhibited higher osteogenesis-related protein expression than PCL-only scaffolds, further enhanced by pulsed electromagnetic field (PEMF) application. The application of PEMF stimulation within aligned RGO-NFs presents a potentially more efficient alternative to existing methods, offering a novel, non-invasive therapeutic strategy for bone defect regeneration.